Drug-related problems among older people with dementia: A systematic review - Ng, Qlaementine Xue Qin; Long, Chiau Ming *; Mohd Shahezwan, Abdul Wahab; Tan, Ching Siang; Yuda, Ana; Hermansyah, Andi (Elsevier, 2023)
Introduction: Dementia is a disorder that causes a decline of cognitive function, and it affects millions of people worldwide. Increased availability of medications used to treat dementia will inevitably increase the likelihood of drug-related problems (DRPs).